The role of uncentrifuged urine microscopy in the diagnosis of urinary tract infection (Tanzania Medical Journal, 2015)
Background: Urinary tract infection (UTI) is one of the most common nosocomial bacterial infections prevalent in both males and females. UTI is diagnosed on the basis of clinical symptoms, microscopy and culture of urine. This study was done to establish the role of the routine uncentrifuged urine microscopy using culture as gold standard at Bugando Medical Centre. Methods: A total of 389 urine specimens were processed. Urine microscopy was done to all specimens to determine WBC/high powerfield. All specimens were cultured on Mackonkey, Blood agar and CLED. The presence of 5 or more WBC/HPF was considered as positive and presence of 105CFU/ml was reported as significant bacteriuria. Urine microscopy results and culture results were statistically compared using p?0.05 as significant. Results: The prevalence of UTI by culture and urine microscopy was 38.8% and 13.3% respectively. Using culture as gold standard the sensitivity, specificity and positive predictive value of uncentrifuged urine were 34%, 84% and 58% respectively. There was significant association between presence of ?5 WBC/HPF and positive urine culture (? 10 5 CFU/ml) p=0.001. Escherichia coli contributed 60% of microorganisms causing UTI at Bugando Medical Centre. Conclusion and recommendations: The uncentrifuged urine microscopy has little sensitivity in the diagnosis of UTI in our setting. This method should be used as screening but urine culture should be performed in all patients suspected to have Urinary tract infections.